Community childhood obesity assessment in elementary school, anthropometric indices as screening tools: a community cross-sectional study in Indonesia - Iche Andriyani Liberty; Indri Seta Septadina; Muhammad Qurhanul Rizqie; Mariana Mariana; Pariyana Pariyana; Resy Amalia; Hamzah Hasyim (BMJ Publishing Group, 2024)
Background Representative anthropometric epidemiological data are needed to formulate screening and intervention methods to prevent obesity in children. This study aims to conduct community childhood obesity assessment in elementary school based on anthropometric measurements and evaluate its predictive value.Methods This cross-sectional study was carried out in Palembang, Indonesia, and involved 1180 elementary school students. The anthropometric parameters were divided into (1) basic data: stature, weight and waist circumference (WC), hip circumference (HC); (2) structural dimensions: the segmental dimensions of head-neck, trunk, upper extremity, hand, lower extremity and foot and (3) postural dimensions: the relative spacial dimensions when standing. Six anthropometric indices were considered: body mass index, waist-to-hip ratio (WHR), waist-to-height ratio (WHtR), Conicity Index (CI), Body Adiposity Index (BAI) and Tri-ponderal Mass Index (TMI).Results The proportion of overweight and obesity was 50.17% (n=592) and normal weight was 49.83% (n=588). The mean age was 8.26±1.71 years. The averages of all measured indices in overweight/obese versus normal weight were significant difference among boys and girls in height, weight, WC, HC, neck circumference, WHR, WHtR, neck-to-height ratio, BAI, TMI and CI (p<0.05 for all). TMI was the best predictor of obesity based on area under the curve (AUC) values, both in boys (sensitivity=90.48; specificity=91.53; AUC=0.975) and in girls (sensitivity=90.28; specificity=90.00; AUC=0.968).Conclusions A trustworthy anthropometric database of primary school students might be a helpful local resource when working on projects involving children. In order to improve the quality of life through better-suited and secure products and environmental designs, it is crucial to build an anthropometric database.